CUBAN NINETEENTH-CENTURY THOUGHT: CONTRIBUTION TO PHYSICAL EDUCATION AND SPORTS - Rodríguez González, Reynier (2017)
The objective of this article is to explore the existing relationships between the humanistic formation and physical culture in the Cuban pedagogical thinking during the nineteenth century. With this goal in mind, a bibliographical search was performed including the most relevant authors who had addressed the topic and including some sources of their thinking, in order to better interpret and assess this topic. The integrative, selective and critical approach of Cuban pedagogical thinking from that era was verified in its sociocultural, universal, and autochthonous character, patent in different actions meant to introduce the humanistic model and physical culture into the formative process. We show some shortcomings in the present approach to those elements associated with physical culture in Cuban history, and the lack of solid discussion about 19th century Cuban teachers’ contributions to the humanistic model and its close relation to physical culture. Future research topics are proposed as a possible contribution to training professionals in this field.